PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT TUNAS ABADI MAKMUR (TAM) DIVISI SONY XPERIA SURABAYA - YULIANTO, EKO (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2014)
ABSTRACTOne can affect employees performance is the work motivation. Work motivation is influenced by many factors whether internal or external factors. To achieve that purpose so the company must have the effort to aims the purpose that is provide insentives or appreciation in approriate, because employees performance not coming by accidental. This research conducted to know how the effect of work motivation toward employees performance of PT. Tunas Abadi Makmur Surabaya (TAM) Sony Xperia Division Surabaya. This research aims to analyze employees performance at PT. Tunas Abadi Makmur (TAM) Divisi Sony Xperia Surabaya. By using approach motivation variable. This research was carried out on the perspective of employee performance. This research quantitative descriptive of analysis method. Processing data is using SPSS statistical tool with a simple linear regression analysis model. The samples used were 31 respondents from the general population. The results of the study explained that work motivation have a significant influence on employee performance. Work motivation gain 211 poin or 42,5% from the responden who agreed. At the same tine employees performance gain 105 poin or 56,4%. So from this result can be concluded that work motivation have a significant influence on employee performance. These results suggest that the company management should be able to implement policies related to motivation to improved employee performance.Keywords: Performance, Motivation